Oil Spill(over)s : Linkages in Petroleum Product Pricing Policies in West African Countries - El Harrak, Mohamed (IMF Working Papers; Working Paper, 2011)
This paper addresses a number of issues regarding petroleum product pricing in Western Africaemphasizing international spillovers. We use panel unit root rests and long-run modeling based on vector error correction models to assess links and convergence in petroleum product prices across countries. Our results indicate that in general over the long-run there is convergence in prices across the countries. The estimation results for gasoline and diesel prices suggest the presence of long-run links between retail prices among the different country groupings with long-run multipliers ranging from 11 to -6.66. The speed of Adjustment to equilibrium varies significantly according to the countrygroupings considered. In contrast, the econometric results for kerosene prices not only indicate a weaker link between prices across countries, but also a much slower adjustment to equilibrium. Inlight of these important spillovers, the need to better coordinate pricing s and tax policies towards petroleum products at the regional level becomes apparent.